Spain 1935: A lost opportunity - Luis Peral (The Journal of European Economic History (JEEH), 2025)
A close and unbiased analysis of the economic policies of the Second Spanish Republic shows a remarkable continuity between the fiscal and monetary policies of all the republican governments, whatever their political ideology. While Spain was less affected than other nations by the Great Depression, its impact was nonetheless felt in some sectors of the Spanish economy like agrarian exports and maritime transport, as well as foreign investment. In any case, at the end of 1935 - after two consecutive years of economic growth and having reached the net domestic product level in real terms of 1929 - Spain was leaving behind the economic crisis. The centre-right government was supported by a parliamentary majority, elected for a period that would finish in November 1937. Their economic programme, while maintaining budget equilibrium, envisaged a set of public investments to promote economic growth and employment, while revising, at the same time, the Constitution and the electoral law. Unfortunately, growing ideological sectarianism in the Spanish political scene, unsurmountable differences between the governing coalition and the irresponsibility of some political leaders led Spain to lose a great opportunity for a better future. In the following months of 1936, political radicalization, sectarian violence and the loss of legal certainty put an end to Spanish political and economic normality. Public order and social coexistence deteriorated severely, a process that culminated in the outbreak of the civil war.
Keywords: 330